Decontamination of SARS-CoV-2 from cold-chain food packaging provides no marginal benefit in risk reduction to food workers. (June 2022) - Sobolik, Julia S.; Sajewski, Elizabeth T.; Jaykus, Lee-Ann; Cooper, D. Kane; Lopman, Ben A.; Kraay, Alicia N.M.; Ryan, P. Barry; Guest, Jodie L.; Webb-Girard, Amy; Leon, Juan S.
Abstract: Countries continue to debate the need for decontamination of cold-chain food packaging to reduce possible severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) fomite transmission among frontline workers. While laboratory-based studies demonstrate persistence of SARS-CoV-2 on surfaces, the likelihood of fomite-mediated transmission under real-life conditions is uncertain. Using a quantitative microbial risk assessment model of a frozen food packaging facility, we simulated 1) SARS-CoV-2 fomite-mediated infection risks following worker exposure to contaminated plastic packaging; and 2) reductions in these risks from masking, handwashing, and vaccination. In a frozen food facility without interventions, SARS-CoV-2 infection risk to a susceptible worker from contact with contaminated packaging was 1.5 × 10 −3 per 1h-period (5th – 95th percentile: 9.2 × 10 −6, 1.2 × 10 −2 ). Standard food industry infection control interventions, handwashing and masking, reduced risk (99.4%) to 8.5 × 10 −6 risk per 1h-period (5th – 95th percentile: 2.8 × 10 −8, 6.6 × 10 −5 ). Vaccination of the susceptible worker (two doses Pfizer/Moderna, vaccine effectiveness: 86–99%) with handwashing and masking reduced risk to 5.2 × 10 −7 risk per 1h-period (5th – 95th percentile: 1.8 × 10 −9, 5.4 × 10 −6 ). Simulating increased transmissibility of current and future variants (Delta, Omicron), (2-, 10-fold viral shedding) among a fully vaccinated workforce, handwashing and masking continued to mitigate risk (1.4 × 10 −6 - 8.8 × 10 −6 risk per 1h-period). Additional decontamination of frozen food plastic packaging reduced infection risks to 1.2 × 10 −8 risk per 1h-period (5th – 95th percentile: 1.9 × 10 −11, 9.5 × 10 −8 ). Given that standard infection control interventions reduced risks well below 1 × 10 −4 (World Health Organization water quality risk thresholds), additional packaging decontamination suggest no marginal benefit in risk reduction. Consequences of this decontamination may include increased chemical exposures to workers, food quality and hazard risks to consumers, and unnecessary added costs to governments and the global food industry. Highlights: SARS-CoV-2 infection risk from contact with frozen food packaging is very low. Standard food worker handwashing and masking practices reduce risk by 99.4%. Vaccination, handwashing, and masks mitigate risks from more transmissible variants. Additional packaging decontamination results in minimal risk reduction to workers.